Non-magnetic gradient electromagnetic shielding composite material based on mxene and graphene oxide and preparation method and application thereof
By designing electromagnetic shielding materials with MS thin film and MS layer gradient structure, the problems of high density, easy corrosion and high reflection in the existing technology have been solved, and lightweight, low reflection and high absorption electromagnetic shielding performance has been achieved, which is suitable for aerospace and wearable devices.
Patent Information
- Application Number
- CN202610463745.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-04-09
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2046-04-09
AI Technical Summary
Existing electromagnetic shielding materials rely on magnetic fillers, resulting in high density and easy corrosion. Their high conductivity leads to high reflection, and the utilization rate of MXene waste is low, making it difficult to achieve lightweight, low-reflection, and high-absorption electromagnetic shielding performance.
A non-magnetic gradient electromagnetic shielding composite material is designed, which adopts a three-layer structure of MS thin film, high-concentration MS layer and low-concentration MS layer. It is composed of MXene precipitate, graphene oxide and cellulose nanofibers. Through dielectric spatial gradient distribution design, a wave transmission matching layer, a wave absorption loss layer and a reflection shielding layer are constructed to achieve low reflection and high absorption electromagnetic shielding performance.
It achieves broadband electromagnetic shielding performance with low cost, non-magnetic properties, low reflection, and high absorption. The material is lightweight and has good chemical stability, making it suitable for aerospace and wearable device applications. The process is simple and suitable for large-scale preparation.
Smart Images

Figure CN122121138B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electromagnetic shielding, specifically to a non-magnetic gradient electromagnetic shielding composite material based on MXene and graphene oxide, its preparation method, and its application. Background Technology
[0002] With the rapid development of fifth-generation (5G) mobile communication technology, high-frequency radar detection systems, and flexible wearable electronic devices, electromagnetic waves, while bringing convenience to human life, have also caused electromagnetic radiation pollution. Electromagnetic radiation can not only interfere with the normal operation of precision electronic instruments and cause information leakage, but also pose potential harm to human health. Therefore, the development of high-performance electromagnetic shielding materials that combine lightweight, high efficiency, and flexibility has become an urgent need in the fields of materials science and electronic engineering.
[0003] MXene (a class of two-dimensional transition metal carbides / nitrides / carbonitrides) is currently recognized as one of the most promising electromagnetic shielding materials. Due to its unique layered structure, extremely high metallic conductivity (up to 20,000 S / cm or more), and abundant hydrophilic functional groups on the surface, MXene is widely used to prepare electromagnetic shielding materials such as thin films and aerogels.
[0004] However, existing technologies have the following three significant limitations: (1) Traditional electromagnetic shielding materials that rely primarily on absorption depend on magnetic fillers, resulting in high density and susceptibility to corrosion. To improve impedance matching and reduce reflectivity, existing technologies typically introduce magnetic metal particles (such as iron, cobalt, and nickel nanoparticles) or ferrites (such as Fe3O4) into the matrix. Although magnetic loss can improve absorption performance, the introduction of magnetic fillers leads to: ① a significant increase in the density of composite materials, making it difficult to meet the stringent requirements for lightweighting in aerospace and wearable devices; ② magnetic metals are highly susceptible to oxidation and corrosion in humid or corrosive environments, causing shielding performance to degrade over time; ③ magnetic materials are limited by the Snoek limit at high frequencies, resulting in a sharp decrease in permeability and affecting high-frequency absorption.
[0005] (2) The problem of high reflection caused by high conductivity. If no magnetic material is added, relying solely on the high conductivity of MXene, according to electromagnetic shielding theory, incident electromagnetic waves will be strongly reflected at the material surface. Existing non-magnetic MXene-based composite materials often struggle to maintain high shielding effectiveness (SE). T While achieving low reflectivity, the homogeneous high conductivity structure suffers from severe impedance mismatch, which can easily cause secondary reflection pollution of electromagnetic waves and is not conducive to electromagnetic environment management in practical application scenarios.
[0006] (3) High preparation cost and low raw material utilization. Currently, the preparation process for high-performance MXene (such as the LiF / HCl etching method) typically extracts only a small layer of MXene dispersion from the supernatant after centrifugation, while the bottom precipitate (i.e., incompletely peeled MXene or large particles, referred to as MXene waste, MS), which accounts for the majority of the raw material mass, is usually discarded as waste. This not only results in a huge waste of expensive titanium sources (Ti3AlC2MAX powder) and etching reagents, but also severely limits the low-cost, large-scale application of MXene materials. It is worth noting that the measured conductivity of this type of MXene precipitate waste is as high as 2.1 × 10⁻⁶. 5 S / m has the potential to be used as a high-performance electromagnetic shielding filler.
[0007] In summary, there is an urgent need in the existing technology for a novel electromagnetic shielding composite material and its preparation method that can effectively utilize MXene waste to reduce costs, does not rely on magnetic fillers, and solves the impedance mismatch problem through microstructure design, thereby achieving non-magnetic, low-reflection, and high-absorption characteristics. Summary of the Invention
[0008] The purpose of this invention is to overcome the shortcomings of existing technologies and provide a non-magnetic gradient electromagnetic shielding composite material based on MXene and graphene oxide, its preparation method, and its applications. The non-magnetic gradient electromagnetic shielding composite material of this invention can achieve broadband electromagnetic shielding performance with low cost, non-magnetic properties, low reflection, and high absorption.
[0009] To achieve the above objectives, the technical solution designed by the present invention is as follows: This invention provides a non-magnetic gradient electromagnetic shielding composite material, which comprises, from bottom to top, an MS thin film, a high-concentration MS layer, and a low-concentration MS layer; The MS thin film is made from MXene precipitate, which has an electrical conductivity of 2.0 × 10⁻⁶. 5 ~2.2×10 5 Sm -1 ; The raw materials for both the high-concentration MS layer and the low-concentration MS layer are composed of MXene precipitate, graphene oxide, and cellulose nanofibers. In the high-concentration MS layer, the mass ratio of MXene precipitate, graphene oxide, and cellulose nanofibers is 3~3.5:1.5~2:5; In the low-concentration MS layer, the mass ratio of MXene precipitate, graphene oxide, and cellulose nanofibers is 0.5~2.5:2.5~4.5:5.
[0010] Furthermore, the MXene precipitate is Ti3C2T. xThe powder was etched and repeatedly centrifuged and washed to obtain a precipitate.
[0011] Furthermore, the thickness of the MS film is 20~30 μm, the thickness of the high-concentration MS layer is 2~4 mm, and the thickness of the low-concentration MS layer is 2~4 mm.
[0012] Furthermore, in the high-concentration MS layer, the mass ratio of MXene precipitate, graphene oxide, and cellulose nanofibers is 3:2:5; In the low-concentration MS layer, the mass ratio of MXene precipitate, graphene oxide, and cellulose nanofibers is 1:4:5.
[0013] The present invention also provides a method for preparing the aforementioned composite material, comprising the following steps: (1) Mix and stir MXene precipitate slurry (MXene precipitate slurry is slurry containing MXene precipitate) and water to obtain MS aqueous dispersion. After filtering the MS aqueous dispersion, vacuum filter it to obtain MS film. (2) Add graphene oxide to water to obtain graphene oxide dispersion, and add cellulose nanofibers to water to obtain cellulose nanofiber dispersion; (3) According to the above mass ratio in the high-concentration MS layer, mix MXene precipitate slurry, graphene oxide dispersion and cellulose nanofiber dispersion to obtain high-concentration MS dispersion; (4) According to the mass ratio in the low-concentration MS layer mentioned above, mix MXene precipitate slurry, graphene oxide dispersion and cellulose nanofiber dispersion to obtain low-concentration MS dispersion; (5) Place the MS film in a mold, add a high concentration MS dispersion, and freeze the mold in liquid nitrogen to form a high concentration MS layer on the surface of the MS film; (6) Add a low concentration MS dispersion to the mold, place the mold in liquid nitrogen for freezing, and a low concentration MS layer is formed on the surface of the high concentration MS layer. Transfer the mold to a vacuum freeze dryer for freeze drying. After drying, take the sample out of the mold to obtain a non-magnetic gradient electromagnetic shielding composite material.
[0014] Furthermore, the preparation process of the MXene precipitate slurry is as follows: S1. Mix and stir lithium fluoride and hydrochloric acid solution to obtain etching solution; S2, Ti3C2T x The powder is added to the etching solution and stirred for etching. S3. After etching, the resulting mixture is repeatedly centrifuged and washed, and the precipitate is collected to obtain MXene precipitate slurry.
[0015] Furthermore, in step S1, the concentration of the hydrochloric acid solution is 8-10 M, and the mass-to-volume ratio of lithium fluoride to hydrochloric acid solution is 1:10-15. In step S2, the etching temperature is 45~55℃ and the etching time is 30~40 h; In step S3, the supernatant is repeatedly centrifuged and washed until the pH of the supernatant is 6-6.5.
[0016] Furthermore, in step (1), the mixing speed is 2000~2200 rpm, the mixing time is 30~40 min, and the concentration of MXene precipitate in the MXene precipitate slurry is 80~85 mg / mL; In step (2), the concentration of the graphene oxide dispersion is 10~15 mg / mL, and the concentration of the cellulose nanofiber dispersion is 40~45 mg / mL. In step (6), the freeze-drying conditions are -50~-70℃, 1~2 Pa, and 20~25 h.
[0017] Furthermore, the mixing speed is 2000 rpm, and the mixing time is 30 min; In the MXene precipitate slurry, the concentration of MXene precipitate is 80 mg / mL, the concentration of graphene oxide dispersion is 10 mg / mL, and the concentration of cellulose nanofiber dispersion is 40 mg / mL. The freeze-drying conditions are -70℃, 1~2 Pa, 24 h.
[0018] The present invention also provides an application of the aforementioned composite material in electromagnetic shielding.
[0019] The principle of this invention: The electromagnetic shielding mechanism of the three-layer gradient structure MS / GO / CNF composite aerogel prepared in this invention is based on the dielectric spatial gradient distribution design concept. It constructs a three-layer functional structure from the outside in: a wave transmission matching layer, a wave absorption loss layer, and a reflection shielding layer. The specific working principle is as follows: (1) Top layer (wave-transmitting / impedance matching layer): It is constructed with MS / GO / CNF aerogel with low MS content (such as M-2, 20%). This layer has low conductivity and is close to free space impedance, which can minimize the initial reflection of electromagnetic waves on the material surface and allow incident electromagnetic waves to penetrate smoothly into the material.
[0020] (2) Intermediate layer (wave absorption / dielectric loss layer): Constructed using MS / GO / CNF aerogel with high MS content (e.g., M-6, 60 wt%), this layer has a dense conductive network and abundant interfacial polarization effects. On the one hand, the oriented porous microstructure formed by the directional freezing process extends the transmission path of electromagnetic waves, promoting multiple reflections and scattering; on the other hand, the numerous heterogeneous interfaces between MS particles, GO sheets and CNF generate significant interfacial polarization (Maxwell-Wagner effect) and dipole polarization under the action of alternating electromagnetic fields, efficiently converting electromagnetic energy into heat energy dissipation.
[0021] (3) Bottom layer (reflection / terminal shielding layer): composed of pure MS thin film prepared by vacuum filtration, with a thickness of 20 μm and an electrical conductivity of 2.1 × 10⁻⁶. 5 S / m, forming a dense conductive layer, which acts as the final shielding barrier. This layer efficiently reflects any residual electromagnetic waves from the first two layers, causing them to re-enter the intermediate absorbing layer for secondary loss, rather than escaping outwards. This ensures high overall shielding effectiveness (SE). T At the same time, it significantly reduces secondary reflections from the incident surface.
[0022] The introduction of directional freezing technology (liquid nitrogen, -196℃) creates anisotropic pore structures arranged along the thickness direction within each layer, increasing the specific surface area and interfacial polarization area, and further enhancing the dielectric loss mechanism. The synergistic effect of overall gradient impedance and dielectric loss enables the material to achieve high-performance electromagnetic shielding based primarily on absorption without introducing any magnetic fillers.
[0023] The beneficial effects of this invention are: (1) Turning waste into treasure, significantly reducing preparation costs and greatly improving raw material utilization. This invention successfully utilizes the bottom sediment (MS) waste that is usually discarded directly during the MXene preparation process as the main functional filler to prepare it into a high-performance electromagnetic shielding material, solving the problem of disposing of large amounts of MS slurry. Compared with the prior art that only uses expensive MXene supernatant, this invention greatly improves the raw material utilization rate and significantly reduces the preparation cost, opening up a new path for the low-cost, large-scale industrial application of MXene-based electromagnetic shielding materials.
[0024] (2) The unique three-layer gradient structure achieves excellent electromagnetic shielding performance with low reflection and high absorption. Taking the optimal sample GMG-20 / 60 as an example, its total shielding effectiveness (SE) is... T Within the 8.2–12.4 GHz (X-band) range, it achieves an absorption coefficient (A) exceeding 80 dB, a high absorption coefficient (A) of 0.84, and a low reflectivity (R) of 0.16, truly realizing green electromagnetic shielding primarily based on absorption and effectively avoiding secondary electromagnetic wave reflection pollution. In contrast, homogeneous aerogels (MG series), even at the highest MS content (MG-60, SE...),...T The reflectivity of the inverse gradient structure is 42.5 dB, and its reflectivity is still relatively high (R>0.6), with limited absorption contribution. However, the reflectivity of the inverse gradient structure is significantly higher (R>0.9) due to the orientation of the MS highly conductive film toward the incident surface, which verifies the criticality of gradient direction design.
[0025] (3) Non-magnetic lightweight design overcomes the shortcomings of traditional magnetic shielding materials, such as high density and poor weather resistance. This invention is completely free of high-density magnetic metal fillers such as iron, cobalt, and nickel. It uses low-density CNF aerogel as the skeleton, and the material as a whole has extremely low density, which fully meets the stringent requirements of aerospace and wearable devices for lightweight materials. At the same time, it avoids the problem of easy oxidation and corrosion of magnetic fillers in humid environments, endows the material with excellent chemical stability in complex environments, and is not limited by the Snoek limit. It also maintains excellent shielding performance in the high-frequency band (X-band and above).
[0026] (4) The process is simple, has good repeatability, and is suitable for large-scale preparation. This invention uses mature processes such as vacuum filtration, directional freezing, and vacuum freeze drying, with clear steps and controllable parameters.
[0027] (5) Synergistic effect of functional components. GO sheets act as two-dimensional conductive bridging components in the CNF three-dimensional network framework, forming a multi-level conductive network with MS particles, which improves the overall conductivity and dielectric loss capability; CNF provides a biocompatible and sustainable water-soluble matrix, which has good hydrogen bond interaction with MS and GO, and helps to build a uniform and stable mixed dispersion system; while the anisotropic pore structure endowed by the directional freezing process further increases the internal scattering area. The three work together to achieve excellent electromagnetic shielding performance. Attached Figure Description
[0028] Figure 1 Electron microscope image of the non-magnetic gradient electromagnetic shielding composite material used in the embodiment; Figure 2 The top microscopic images are of the non-magnetic electromagnetic shielding composite materials used in Comparative Examples 1-6. In the diagram, a is MG-10, b is MG-20, c is MG-30, d is MG-40, e is MG-50, and f is MG-60. Figure 3 The figure shows the conductivity measurement results for a homogeneous MS / GO / CNF aerogel. Figure 4 The graph shows the electromagnetic shielding performance results of the non-magnetic electromagnetic shielding composite materials used in Comparative Examples 1-6. Figure 5 The graphs show the positive gradient electromagnetic shielding performance results of the non-magnetic gradient electromagnetic shielding composite materials in Examples 2-6. Figure 6The graphs show the inverse gradient electromagnetic shielding performance results of the non-magnetic gradient electromagnetic shielding composite materials in Examples 2-6. Figure 7 The graph shows the positive gradient electromagnetic shielding performance results of the non-magnetic electromagnetic shielding composite materials used in Comparative Examples 7-11. Figure 8 The figure shows the thickness optimization results of GMG-20 / 60, a non-magnetic gradient electromagnetic shielding composite material. In the figures, GMG-20 / 60-t(1 / 2) consists of a low-concentration MS layer M-2 with a thickness of 1 mm and a high-concentration MS layer M-6 with a thickness of 2 mm; GMG-20 / 60-t(2 / 2) consists of a low-concentration MS layer M-2 with a thickness of 2 mm and a high-concentration MS layer M-6 with a thickness of 2 mm; GMG-20 / 60-t(2 / 3) consists of a low-concentration MS layer M-2 with a thickness of 2 mm and a high-concentration MS layer M-6 with a thickness of 3 mm; GMG-20 / 60-t(2 / 4) consists of a low-concentration MS layer M-2 with a thickness of 2 mm and a high-concentration MS layer M-6 with a thickness of 4 mm; GMG-20 / 60-t(3 / 4) consists of a low-concentration MS layer M-2 with a thickness of 3 mm and a high-concentration MS layer M-6 with a thickness of 4 mm; GMG-20 / 60-t(4 / 4) consists of a low-concentration MS layer M-2 with a thickness of 4 mm. The thickness of the high-concentration MS layer M-6 is 4 mm. Detailed Implementation
[0029] The present invention will now be described in further detail with reference to specific embodiments, so that those skilled in the art can understand it.
[0030] Example 1 Preparation of raw materials 1. Preparation of MXene precipitate slurry (MS slurry) (1) Add 16 g LiF to 200 mL 9 M HCl solution and stir for 30 min at room temperature to form a uniform etching solution.
[0031] (2) 10 g of Ti3AlC2 (MAX powder) was slowly added to the uniform etching solution. After the MAX powder was completely added, the reaction system was transferred to a 50°C water bath and continuously stirred for 36 h for etching.
[0032] (3) After etching, the resulting mixture was centrifuged (3500 rpm) and repeatedly washed with deionized water until the supernatant was transparent and the pH was close to neutral (pH 6~6.5). A black precipitate was found at the bottom of the centrifuge tube. The black precipitate at the bottom was collected as MS slurry (MXene precipitate slurry). The concentration of MXene precipitate (MS) in the MS slurry was measured to be 80 mg / ml.
[0033] MS slurry was vacuum filtered to form a 20-micron film, and the conductivity of the MS slurry was measured to be 2.1 × 10⁻⁶ using an RTS-9 four-probe conductivity meter. 5 S m -1 .
[0034] 2. Preparation of GO dispersion: Graphene oxide (GO) was dispersed in deionized water to obtain a GO dispersion of 10 mg / mL.
[0035] 3. Preparation of CNF dispersion: Cellulose nanofibers (CNF) were dispersed in water to obtain a CNF dispersion of 40 mg / mL. Example 2 Preparation of nonmagnetic gradient electromagnetic shielding composite material GMG-10 / 60 The non-magnetic gradient electromagnetic shielding composite material GMG-10 / 60 in this embodiment is a gradient structure MS / GO / CNF composite aerogel GMG-10 / 60, which includes, from bottom to top, an MS film, a high-concentration MS layer M-6, and a low-concentration MS layer M-1. The preparation process is as follows: 1. MS film preparation: 0.5 ml of MS slurry from Example 1 and 39.5 ml of deionized water were added to a vacuum mixing tank and placed in a planetary stirrer for continuous stirring at 2000 rpm for 30 min to obtain an MS aqueous dispersion with a concentration of 1 mg / ml. 40 ml of the MS aqueous dispersion was taken and vacuum filtered through a microporous membrane with a pore size of 0.22 μm to obtain a 20 μm MS film.
[0036] 2. Preparation of dispersion M-6: Take 3.75 mL of MS slurry (MS mass is 0.30 g), 20.0 mL of GO dispersion (GO mass is 0.2 g) and 12.5 mL of CNF dispersion (CNF mass is 0.5 g), mix them evenly, and add 13.75 mL of deionized water to 50 mL to obtain dispersion M-6, in which the mass of MS is 60% of the total mass of MS and GO, and the concentration of CNF is 10 mg / mL.
[0037] 3. Preparation of dispersion M-1: Take 0.625 mL of MS slurry (MS mass is 0.05 g), 45.0 mL of GO dispersion (GO mass is 0.45 g) and 12.5 mL of CNF dispersion (CNF mass is 0.5 g) and mix them evenly. The total volume of the three is 58.125 mL, which is dispersion M-1. The mass of MS is 10% of the total mass of MS and GO.
[0038] 4. Preparation of high-concentration MS layer M-6: The prepared MS film was placed in a mold consisting of a copper substrate and polytetrafluoroethylene sidewalls as the bottom layer. 7 ml of pre-prepared dispersion M-6 was added to the mold as an intermediate layer covering the bottom film. The mold was then immersed in liquid nitrogen (-196℃) to establish a vertical temperature gradient, forming a high-concentration MS layer M-6 (2 mm) on the surface of the MS film.
[0039] 5. Preparation of low-concentration MS layer M-1: 7 ml of dispersion M-1 was added to a mold and placed as the top layer covering the frozen intermediate layer. The mold was then immersed in liquid nitrogen (-196℃). After the sample was completely frozen, a low-concentration MS layer M-1 (2 mm) was formed on the surface of the high-concentration MS layer M-6. The mold was then transferred to a vacuum freeze dryer for freeze-drying (-70℃, <2 Pa) for 24 h. After drying, the sample was removed from the mold, yielding a gradient structure MS / GO / CNF composite aerogel GMG-10 / 60 with a three-layer structure, i.e., a non-magnetic gradient electromagnetic shielding composite material GMG-10 / 60.
[0040] Example 3 Preparation of nonmagnetic gradient electromagnetic shielding composite material GMG-20 / 60 The non-magnetic gradient electromagnetic shielding composite material GMG-20 / 60 in this embodiment is a gradient structure MS / GO / CNF composite aerogel GMG-20 / 60, which includes, from bottom to top, an MS film, a high-concentration MS layer M-6, and a low-concentration MS layer M-2. The preparation process is as follows: 1. MS thin film preparation: Same as in Example 2.
[0041] 2. Preparation of dispersion M-6: Same as in Example 2.
[0042] 3. Preparation of dispersion M-2: Take 1.25 mL of MS slurry (MS mass is 0.1 g), 40.0 mL of GO dispersion (GO mass is 0.40 g) and 12.5 mL of CNF dispersion (CNF mass is 0.5 g) and mix them evenly. The total volume of the three is 53.75 mL, which is dispersion M-2. The mass of MS is 20% of the total mass of MS and GO.
[0043] 4. Preparation of high-concentration MS layer M-6: Same as in Example 2.
[0044] 5. Preparation of low-concentration MS layer M-2: The method is the same as in Example 2, except that dispersion M-2 is used instead of dispersion M-1 to obtain a gradient structure MS / GO / CNF composite aerogel GMG-20 / 60 with a three-layer structure, namely, non-magnetic gradient electromagnetic shielding composite material GMG-20 / 60.
[0045] Example 4 Preparation of nonmagnetic gradient electromagnetic shielding composite material GMG-30 / 60 The non-magnetic gradient electromagnetic shielding composite material GMG-30 / 60 in this embodiment is a gradient structure MS / GO / CNF composite aerogel GMG-30 / 60, which includes, from bottom to top, an MS film, a high-concentration MS layer M-6, and a low-concentration MS layer M-3. The preparation process is as follows: 1. MS thin film preparation: Same as in Example 2.
[0046] 2. Preparation of dispersion M-6: Same as in Example 2.
[0047] 3. Preparation of dispersion M-3: Take 1.875 mL of MS slurry (MS mass is 0.15 g), 35.0 mL of GO dispersion (GO mass is 0.35 g), and 12.5 mL of CNF dispersion (CNF mass is 0.5 g) and mix them evenly. The total volume of the three is 49.375 mL. Add 0.625 mL of deionized water to 50 mL to obtain dispersion M-3. The mass of MS is 30% of the total mass of MS and GO, and the concentration of CNF is 10 mg / mL.
[0048] 4. Preparation of high-concentration MS layer M-6: Same as in Example 2.
[0049] 5. Preparation of low-concentration MS layer M-3: The method is the same as in Example 2, except that dispersion M-3 is used instead of dispersion M-1 to obtain a gradient structure MS / GO / CNF composite aerogel GMG-30 / 60 with a three-layer structure, namely, non-magnetic gradient electromagnetic shielding composite material GMG-30 / 60.
[0050] Example 5 Preparation of nonmagnetic gradient electromagnetic shielding composite material GMG-40 / 60 The non-magnetic gradient electromagnetic shielding composite material GMG-40 / 60 in this embodiment is a gradient structure MS / GO / CNF composite aerogel GMG-40 / 60, which includes, from bottom to top, an MS film, a high-concentration MS layer M-6, and a low-concentration MS layer M-4. The preparation process is as follows: 1. MS thin film preparation: Same as in Example 2.
[0051] 2. Preparation of dispersion M-6: Same as in Example 2.
[0052] 3. Preparation of dispersion M-4: Take 2.5 mL of MS slurry (MS mass is 0.2 g), 30.0 mL of GO dispersion (GO mass is 0.30 g), and 12.5 mL of CNF dispersion (CNF mass is 0.5 g) and mix them evenly. The total volume of the three is 45 mL. Add 5 mL of deionized water to 50 mL to obtain dispersion M-4. The mass of MS is 40% of the total mass of MS and GO, and the concentration of CNF is 10 mg / mL.
[0053] 4. Preparation of high-concentration MS layer M-6: Same as in Example 2.
[0054] 5. Preparation of low-concentration MS layer M-4: The method is the same as in Example 2, except that dispersion M-4 is used instead of dispersion M-1 to obtain a gradient structure MS / GO / CNF composite aerogel GMG-40 / 60 with a three-layer structure, namely, non-magnetic gradient electromagnetic shielding composite material GMG-40 / 60.
[0055] Example 6 Preparation of nonmagnetic gradient electromagnetic shielding composite material GMG-50 / 60 The non-magnetic gradient electromagnetic shielding composite material GMG-50 / 60 in this embodiment is a gradient structure MS / GO / CNF composite aerogel GMG-50 / 60, which includes, from bottom to top, an MS film, a high-concentration MS layer M-6, and a low-concentration MS layer M-5. The preparation process is as follows: 1. MS thin film preparation: Same as in Example 2.
[0056] 2. Preparation of dispersion M-6: Same as in Example 2.
[0057] 3. Preparation of dispersion M-5: Take 3.125 mL of MS slurry (MS mass is 0.25 g), 25.0 mL of GO dispersion (GO mass is 0.25 g), and 12.5 mL of CNF dispersion (CNF mass is 0.5 g) and mix them evenly. The total volume of the three is 40.625 mL. Add 9.375 mL of deionized water to 50 mL to obtain dispersion M-5. The mass of MS is 50% of the total mass of MS and GO, and the concentration of CNF is 10 mg / mL.
[0058] 4. Preparation of high-concentration MS layer M-6: Same as in Example 2.
[0059] 5. Preparation of low-concentration MS layer M-5: The method is the same as in Example 2, except that dispersion M-5 is used instead of dispersion M-1 to obtain a gradient structure MS / GO / CNF composite aerogel GMG-50 / 60 with a three-layer structure, namely, non-magnetic gradient electromagnetic shielding composite material GMG-50 / 60.
[0060] Comparative Example 1 Preparation of non-magnetic electromagnetic shielding composite material MG-10 The non-magnetic electromagnetic shielding composite material MG-10 in this embodiment is a homogeneous MS / GO / CNF aerogel MG-10, composed of an MS layer M-1. The preparation process is as follows: 1. Preparation of dispersion M-1: Same as in Example 2.
[0061] 2. Preparation of MS layer M-1: A homogeneous MS / GO / CNF aerogel was prepared using a directional freezing strategy combined with vacuum freeze-drying. 14 ml of dispersion M-1 was poured into a mold consisting of a copper substrate and polytetrafluoroethylene sidewalls, and the entire mold was immersed in liquid nitrogen (-196℃) to establish a vertical temperature gradient. After the sample was completely frozen, an MS layer M-1 (4 mm) was formed. This layer was then freeze-dried in a vacuum freeze dryer (-70℃, <2 Pa) for 24 h to obtain the homogeneous MS / GO / CNF aerogel MG-10, i.e., the non-magnetic electromagnetic shielding composite material MG-10.
[0062] Comparative Example 2 Preparation of non-magnetic electromagnetic shielding composite material MG-20 The non-magnetic electromagnetic shielding composite material MC2 in this embodiment is a homogeneous MS / GO / CNF aerogel MC2, composed of an MS layer M-2. The preparation process is as follows: 1. Preparation of dispersion M-2: Same as in Example 3.
[0063] 2. Preparation of MS layer M-2: The method is the same as that of Comparative Example 1, except that dispersion M-2 is used instead of dispersion M-1 to obtain homogeneous MS / GO / CNF aerogel MG-20, i.e. non-magnetic electromagnetic shielding composite material MG-20.
[0064] Comparative Example 3 Preparation of non-magnetic electromagnetic shielding composite material MG-30 The non-magnetic electromagnetic shielding composite material MC3 in this embodiment is a homogeneous MS / GO / CNF aerogel MC3, composed of an MS layer M-3. The preparation process is as follows: 1. Preparation of dispersion M-3: Same as in Example 4.
[0065] 2. Preparation of MS layer M-3: The method is the same as that of Comparative Example 1, except that dispersion M-3 is used instead of dispersion M-1 to obtain homogeneous MS / GO / CNF aerogel MG-30, i.e. non-magnetic electromagnetic shielding composite material MG-30.
[0066] Comparative Example 4 Preparation of non-magnetic electromagnetic shielding composite material MG-40 The non-magnetic electromagnetic shielding composite material MC4 in this embodiment is a homogeneous MS / GO / CNF aerogel MC4, composed of an MS layer M-4. The preparation process is as follows: 1. Preparation of dispersion M-4: Same as in Example 5.
[0067] 2. Preparation of MS layer M-4: The method is the same as that of Comparative Example 1, except that dispersion M-4 is used instead of dispersion M-1 to obtain homogeneous MS / GO / CNF aerogel MG-40, i.e. non-magnetic electromagnetic shielding composite material MG-40.
[0068] Comparative Example 5 Preparation of non-magnetic electromagnetic shielding composite material MG-50 The non-magnetic electromagnetic shielding composite material MC5 in this embodiment is a homogeneous MS / GO / CNF aerogel MC5, composed of an MS layer M-5. The preparation process is as follows: 1. Preparation of dispersion M-5: Same as in Example 6.
[0069] 2. Preparation of MS layer M-5: The method is the same as that of Comparative Example 1, except that dispersion M-5 is used instead of dispersion M-1 to obtain homogeneous MS / GO / CNF aerogel MG-50, i.e. non-magnetic electromagnetic shielding composite material MG-50.
[0070] Comparative Example 6 Preparation of non-magnetic electromagnetic shielding composite material MG-60 The non-magnetic electromagnetic shielding composite material MC6 in this embodiment is a homogeneous MS / GO / CNF aerogel MC6, composed of an MS layer M-6. The preparation process is as follows: 1. Preparation of dispersion M-6: Same as in Example 2.
[0071] 2. Preparation of MS layer M-6: The method is the same as that of Comparative Example 1, except that dispersion M-6 is used instead of dispersion M-1 to obtain homogeneous MS / GO / CNF aerogel MG-60, i.e. non-magnetic electromagnetic shielding composite material MG-60.
[0072] Comparative Example 7 Preparation of non-magnetic electromagnetic shielding composite material DMG-10 / 60 The non-magnetic electromagnetic shielding composite material DMG-10 / 60 in this comparative example is a two-layer gradient structure MS / GO / CNF aerogel DMG-10 / 60, which includes a high-concentration MS layer M-6 and a low-concentration MS layer M-1 arranged sequentially from bottom to top. The non-magnetic electromagnetic shielding composite material MC10 / 60 in this comparative example is the same as that in Example 2, except that it does not include the MS film.
[0073] Comparative Example 8 Preparation of non-magnetic electromagnetic shielding composite material DMG-20 / 60 The non-magnetic electromagnetic shielding composite material DMG-20 / 60 in this comparative example is a two-layer gradient structure MS / GO / CNF aerogel DMG-20 / 60, which includes a high-concentration MS layer M-6 and a low-concentration MS layer M-2 arranged sequentially from bottom to top. The non-magnetic electromagnetic shielding composite material DMG-20 / 60 in this comparative example is the same as that in Example 3, except that it does not include the MS film.
[0074] Comparative Example 9 Preparation of non-magnetic electromagnetic shielding composite material DMG-30 / 60 The non-magnetic electromagnetic shielding composite material DMG-30 / 60 in this comparative example is a two-layer gradient structure MS / GO / CNF aerogel DMG-30 / 60, which includes a high-concentration MS layer M-6 and a low-concentration MS layer M-3 arranged sequentially from bottom to top. The non-magnetic electromagnetic shielding composite material DMG-30 / 60 in this comparative example is the same as that in Example 4, except that it does not include the MS film.
[0075] Comparative Example 10 Preparation of non-magnetic electromagnetic shielding composite material DMG-40 / 60 The non-magnetic electromagnetic shielding composite material DMG-40 / 60 in this comparative example is a two-layer gradient structure MS / GO / CNF aerogel DMG-40 / 60, which includes a high-concentration MS layer M-6 and a low-concentration MS layer M-4 arranged sequentially from bottom to top. The non-magnetic electromagnetic shielding composite material DMG-40 / 60 in this comparative example is the same as that in Example 5, except that it does not include the MS film.
[0076] Comparative Example 11 Preparation of non-magnetic electromagnetic shielding composite material DMG-50 / 60 The non-magnetic electromagnetic shielding composite material DMG-50 / 60 of this comparative example is a two-layer gradient structure MS / GO / CNF aerogel DMG-50 / 60, which includes a high-concentration MS layer M-6 and a low-concentration MS layer M-5 arranged sequentially from bottom to top. The non-magnetic electromagnetic shielding composite material DMG-50 / 60 of this comparative example is the same as that of Example 6, except that it does not include the MS film.
[0077] Performance testing 1. Microscopic analysis was performed on the non-magnetic gradient electromagnetic shielding composite material of the embodiment, and the results are as follows: Figure 1 As shown, the non-magnetic gradient electromagnetic shielding composite material exhibits a distinct three-layer structure, with the top and middle layers being aerogels with vertical pore structures, and the bottom layer being a dense thin film.
[0078] 2. The tops of the non-magnetic electromagnetic shielding composite materials MG-10, MG-20, MG-30, MG-40, MG-50 and MG-60 of Comparative Examples 1 to 6 were analyzed by scanning electron microscopy.
[0079] The results are as follows Figure 2 As shown, the aerogels all exhibit a typical honeycomb porous structure. A comparison revealed that the pore size gradually decreases with increasing MS content, which is attributed to the varying MS concentrations.
[0080] 3. The electrical conductivity of homogeneous MS / GO / CNF aerogels MG-10, MG-20, MG-30, MG-40, MG-50 and MG-60 was measured.
[0081] The results are as follows Figure 3 As shown, the conductivity of the aerogel increases with increasing MS content, indicating that the conductive network of the aerogel gradually improves. Specifically, when the MS content is 60% (i.e., MG-60 aerogel), the conductivity increases sharply to 8 × 10⁻⁶. -3 S m -1 This indicates that the MG-60 has a good homogeneous conductive network inside, which can better dissipate incident electromagnetic waves.
[0082] 4. Electromagnetic shielding performance measurement (1) The electromagnetic shielding performance of the non-magnetic electromagnetic shielding composite materials MG-10, MG-20, MG-30, MG-40, MG-50 and MG-60 of Comparative Examples 1 to 6 was measured respectively, and SE R It refers to the reflection loss efficiency (the amount of reflected electromagnetic waves, measured in dB), SE A It refers to absorption loss efficiency (the amount of electromagnetic waves absorbed, measured in dB), SE T It is equal to SE R +SE A The total shielding effectiveness (refers to the total amount of electromagnetic waves reflected and absorbed, i.e., how many electromagnetic waves are shielded in total, in dB), R is the reflection coefficient, also known as reflectivity (refers to the proportion of electromagnetic waves reflected, in %), A is the absorption coefficient, absorption rate (refers to the proportion of electromagnetic waves absorbed), and T is the transmission coefficient, transmission rate (refers to the proportion of electromagnetic waves transmitted).
[0083] (2) The electromagnetic shielding performance of the non-magnetic gradient electromagnetic shielding composite materials GMG-10 / 60, GMG-20 / 60, GMG-30 / 60, GMG-40 / 60 and GMG-50 / 60 in Examples 2 to 6 was measured by positive gradient, that is, the electromagnetic wave was incident from the top layer (such as the M-1 layer) of the composite material and the structure was marked as GMG aerogel.
[0084] (3) To further investigate the influence of the gradient structure direction on the electromagnetic shielding mechanism, the incident direction of the electromagnetic wave was adjusted to enter from the bottom of the GMG aerogel, i.e., incident in the reverse gradient direction, and this structure was labeled as RMG aerogel. The reverse gradient electromagnetic shielding performance of the non-magnetic gradient electromagnetic shielding composite materials RMG-10 / 60, RMG-20 / 60, RMG-30 / 60, RMG-40 / 60 and RMG-50 / 60 of Examples 2 to 6 was measured, i.e., the electromagnetic wave was incident from the bottom layer (MS film) of the composite material.
[0085] (4) The electromagnetic shielding performance of the non-magnetic electromagnetic shielding composite materials DMG-10 / 60, DMG-20 / 60, DMG-30 / 60, DMG-40 / 60 and DMG-50 / 60 of Comparative Examples 7 to 11 was measured by positive gradient, that is, the electromagnetic wave was incident from the top layer of the composite material (such as the M-1 layer).
[0086] The results are as follows Figure 4 As shown, with increasing MS content, the SE of homogeneous MS / GO / CNF aerogels... T The shielding effectiveness continued to increase, from 3.5 dB for MG-10 to 42.5 dB for MG-60. Among them, MG-10 aerogel exhibited the highest shielding effectiveness, meeting the standards typically required for commercial electromagnetic shielding materials (SE). T >20 dB). Its SE A It is 37.0 dB, while SE R Only 5.5 dB. Due to SE A Significantly higher than SE R This indicates that the electromagnetic shielding mechanism of this aerogel is mainly based on absorption loss, with reflection loss contributing relatively little. Furthermore, as the MS concentration increases, the transmission coefficient (T) rapidly decreases to near zero, demonstrating a reduction in electromagnetic wave penetration. The absorption coefficient (A) shows a trend of first increasing and then decreasing, reaching a maximum of 0.61, indicating that 61% of the electromagnetic waves are shielded by the aerogel through absorption. This implies that an appropriate MS / GO ratio can modulate the shielding mechanism of the MG aerogel. Simultaneously, the reflection coefficient (R) shows an increasing trend, reaching its highest value (0.71) at the MG-60 aerogel, indicating that 71% of the incident electromagnetic waves are reflected. Therefore, the electromagnetic shielding mechanism of the MG-60 aerogel is primarily dominated by electromagnetic wave reflection.
[0087] The results are as follows Figure 5 As shown, SE represents the reflection loss. R As the MS content in the top layer increases, it first decreases and then increases, while the SE... A Much larger than SE RThis indicates that the electromagnetic wave loss mechanism within the gradient structure MS / GO / CNF composite aerogel is primarily absorption loss. Among all gradient structure MS / GO / CNF composite aerogels, the GMG-20 / 60 aerogel exhibits the highest SE (Sequence of Electromagnetic Waves). R The lowest value (0.7 dB) indicates its strongest absorption loss capability. Further analysis of the power coefficient of GMG aerogel revealed that the transmission coefficient T was close to 0, indicating that almost no electromagnetic waves could penetrate the GMG aerogel. The absorption coefficient A showed a trend of first increasing and then decreasing, with GMG-20 / 60 aerogel exhibiting the highest A (0.84), indicating that 84% of the incident electromagnetic waves were absorbed, demonstrating a shielding characteristic dominated by absorption. Therefore, GMG-20 / 60 aerogel, while maintaining high shielding performance (80.4 dB), meets the requirements of a "green" electromagnetic shielding material (R < 0.5).
[0088] The results are as follows Figure 6 As shown, compared with normally incident GMG aerogel, the SE of RMG-20 / 60 aerogel is... T The changes were minimal, and the overall level remained high, indicating that the gradient structure could maintain good electromagnetic shielding performance under different incident directions. However, its SE R The reflection coefficient of RMG aerogel is significantly improved, reaching 15 dB, indicating a significant enhancement in electromagnetic wave reflection under reverse gradient incidence conditions. This phenomenon is mainly related to the spatial distribution of the conductive network within the gradient structure. When electromagnetic waves enter from the bottom of the RMG aerogel, they first come into contact with the region with a higher content of conductive components and a denser conductive network. This region has higher conductivity and interfacial impedance difference, making it easier to generate electromagnetic wave reflection at the material surface. In contrast, in the forward GMG structure, electromagnetic waves first enter the region with a lower content of conductive components, allowing more electromagnetic waves to penetrate the material interior and undergo multiple scattering and absorption within the porous structure, thus resulting in a relatively smaller reflection contribution. When electromagnetic waves are incident from the MS film side, the reflection coefficient R of the RMG aerogel approaches 1.0, while the absorption coefficient A decreases significantly, indicating that the incident electromagnetic waves are mainly blocked at the material surface and have difficulty penetrating the internal structure for sufficient dissipation. At this point, the electromagnetic shielding mechanism of the RMG aerogel is no longer dominated by absorption but has shifted to being dominated by reflection. The main reason for this phenomenon is that the high conductivity of the MS film causes severe impedance mismatch, resulting in strong reflection of electromagnetic waves in free space at the incident interface. This suppresses absorption processes such as multiple reflections within the aerogel, conductive network losses, and interface polarization losses. These results indicate that the arrangement order of different functional layers in the gradient structure has a significant impact on the electromagnetic wave shielding mechanism. Compared to the reverse gradient structure, the forward gradient design is more conducive to achieving the synergistic effect of surface matching and internal dissipation, thus achieving both high-efficiency shielding and low reflection.
[0089] The results are as follows Figure 7 As shown, compared with GMG aerogel, the SE of the bilayer gradient structure MS / GO / CNF aerogel is... T The absorption coefficient (A) of the bilayer gradient MS / GO / CNF aerogel decreases significantly. However, it is noteworthy that the absorption coefficient (A) of the bilayer gradient MS / GO / CNF aerogel exhibits a similar trend with frequency as that of the GMG aerogel. Specifically, the A of the bilayer gradient MS / GO / CNF aerogel DMG-20 / 60 is the highest at 0.88, similar to that of the GMG-20 / 60 aerogel. This phenomenon indicates that the top M-2 layer and the middle M-6 layer in the GMG-20 / 60 aerogel promote the absorption of incident electromagnetic waves. The bottom MS film ensures the complete dissipation of residual electromagnetic waves within the material, thereby significantly improving the overall shielding performance without affecting the material's absorption performance.
[0090] In summary, through a systematic comparative analysis of monolayer homogeneous aerogels (MG), bilayer gradient aerogels (DMG), and three-layer aerogels with different gradient directions (GMG and RMG), it can be seen that the three-layer positive gradient structure MS / GO / CNF composite aerogel (GMG) constructed in this invention exhibits significant advantages in electromagnetic shielding performance and shielding mechanism regulation. Compared with monolayer homogeneous structures, GMG aerogel maintains a high total shielding effectiveness (SE). T At the same time, it significantly increased the absorption loss ratio (SE). A This effectively reduces reflection loss (SE). R This achieves a shift from reflection-dominated to absorption-dominated shielding. Compared to the double-layer gradient structure, the introduction of a bottom highly conductive MS thin film layer further suppresses electromagnetic wave transmission and promotes multiple reflections and dissipation of incident electromagnetic waves within the material, thus significantly improving overall shielding performance. Furthermore, a comparison of the positive gradient (GMG) and inverse gradient (RMG) structures reveals that the gradient direction has a decisive influence on the electromagnetic shielding mechanism. The positive gradient structure, through the construction of a synergistic structure of "low impedance matching layer – high loss absorption layer – high conductivity reflection layer," allows electromagnetic waves to smoothly enter the material and gradually dissipate, thus achieving both high shielding effectiveness and low reflection characteristics. In contrast, the inverse gradient structure, due to severe interface impedance mismatch, causes strong reflection of electromagnetic waves at the incident interface, suppressing the internal absorption process, resulting in an overall reflection-dominated shielding mechanism.
[0091] Therefore, the three-layer positive gradient MS / GO / CNF composite aerogel proposed in this invention is superior to the existing comparative structures in terms of total electromagnetic shielding effectiveness, and can achieve absorption-dominated "green electromagnetic shielding" characteristics, with better comprehensive performance and broader application prospects.
[0092] 5. For GMG-20 / 60, the best-performing non-magnetic gradient electromagnetic shielding composite material, the thickness of the high-concentration MS layer M-6 and the low-concentration MS layer M-2 were optimized.
[0093] The results are as follows Figure 8 As shown, the reflection coefficient R of GMG-20 / 60 increases with the increase of the M-6 layer thickness, indicating enhanced reflection of electromagnetic waves from its surface. Appropriately increasing the thickness of the M-2 layer can minimize surface reflection, thereby improving electromagnetic wave absorption. Considering both shielding performance and material thickness, a structure with both M-2 and M-6 layers at 2 mm thickness is found to be the optimal configuration.
[0094] All other parts not described in detail are existing technologies. Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention, not all embodiments. People can obtain other embodiments based on these embodiments without creative effort, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A non-magnetic gradient electromagnetic shielding composite material, characterized in that: The composite material comprises, from bottom to top, an MS film, a high-concentration MS layer, and a low-concentration MS layer; The MS film is made from MXene precipitate, and is a dense film obtained by vacuum filtration of the MXene precipitate. The conductivity of the MXene precipitate is 2.0 × 10⁻⁶. 5 ~2.2×10 5 S m -1 The MXene precipitate is a precipitate obtained by sequentially etching Ti3AlC2 powder and repeatedly centrifuging and washing it. The raw materials for both the high-concentration MS layer and the low-concentration MS layer are composed of MXene precipitate, graphene oxide, and cellulose nanofibers. In the high-concentration MS layer, the mass ratio of MXene precipitate, graphene oxide, and cellulose nanofibers is 3~3.5:1.5~2:5; In the low-concentration MS layer, the mass ratio of MXene precipitate, graphene oxide, and cellulose nanofibers is 1~1.5:3.5~4:5; The thickness of the MS film is 20~30 μm, the thickness of the high-concentration MS layer is 2~4 mm, and the thickness of the low-concentration MS layer is 2~4 mm.
2. The composite material according to claim 1, characterized in that: In the high-concentration MS layer, the mass ratio of MXene precipitate, graphene oxide, and cellulose nanofibers is 3:2:
5. In the low-concentration MS layer, the mass ratio of MXene precipitate, graphene oxide, and cellulose nanofibers is 1:4:
5.
3. A method for preparing the composite material according to any one of claims 1 to 2, characterized in that: Includes the following steps: (1) Mix and stir the MXene precipitate slurry with water to obtain an MS aqueous dispersion. After filtering the MS aqueous dispersion, vacuum filter it to obtain an MS film. (2) Add graphene oxide to water to obtain graphene oxide dispersion, and add cellulose nanofibers to water to obtain cellulose nanofiber dispersion; (3) According to the above mass ratio in the high-concentration MS layer, mix MXene precipitate slurry, graphene oxide dispersion and cellulose nanofiber dispersion to obtain high-concentration MS dispersion; (4) According to the mass ratio in the low-concentration MS layer mentioned above, mix MXene precipitate slurry, graphene oxide dispersion and cellulose nanofiber dispersion to obtain low-concentration MS dispersion; (5) Place the MS film in a mold, add a high concentration MS dispersion, and freeze the mold in liquid nitrogen to form a high concentration MS layer on the surface of the MS film; (6) Add a low concentration MS dispersion to the mold, place the mold in liquid nitrogen for freezing, and a low concentration MS layer is formed on the surface of the high concentration MS layer. Transfer the mold to a vacuum freeze dryer for freeze drying. After drying, take the sample out of the mold to obtain a non-magnetic gradient electromagnetic shielding composite material.
4. The preparation method according to claim 3, characterized in that: The preparation process of the MXene precipitate slurry is as follows: S1. Mix and stir lithium fluoride and hydrochloric acid solution to obtain etching solution; S2. Add Ti3AlC2 powder to the etching solution and stir to etch; S3. After etching, the resulting mixture is repeatedly centrifuged and washed, and the precipitate is collected to obtain MXene precipitate slurry.
5. The preparation method according to claim 4, characterized in that: In step S1, the concentration of the hydrochloric acid solution is 8-10 M, and the mass-to-volume ratio of lithium fluoride to hydrochloric acid solution is 1:10-15. In step S2, the etching temperature is 45~55℃ and the etching time is 30~40 h; In step S3, the supernatant is repeatedly centrifuged and washed until the pH of the supernatant is 6-6.
5.
6. The preparation method according to claim 3, characterized in that: In step (1), the mixing speed is 2000~2200 rpm, the mixing time is 30~40 min, and the concentration of MXene precipitate in the MXene precipitate slurry is 80~85 mg / mL; In step (2), the concentration of the graphene oxide dispersion is 10~15 mg / mL, and the concentration of the cellulose nanofiber dispersion is 40~45 mg / mL. In step (6), the freeze-drying conditions are -50~-70℃, 1~2 Pa, and 20~25 h.
7. The preparation method according to claim 6, characterized in that: The mixing speed is 2000 rpm, and the mixing time is 30 min; In the MXene precipitate slurry, the concentration of MXene precipitate is 80 mg / mL, the concentration of graphene oxide dispersion is 10 mg / mL, and the concentration of cellulose nanofiber dispersion is 40 mg / mL. The freeze-drying conditions are -70℃, 1~2 Pa, 24 h.
8. The application of the composite material according to any one of claims 1 to 2 in electromagnetic shielding.
Citation Information
Patent Citations
Low-reflection bacterial cellulose electromagnetic shielding foam as well as preparation method and application thereof
CN121733884A
